2014
DOI: 10.1186/1756-0500-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Expressions and clinical significances of c-MET, p-MET and E2f-1 in human gastric carcinoma

Abstract: BackgroundTo investigate on the expressions and the clinical significances of hepatocyte growth factor receptor (c-MET), phosphorylated c-MET (p-MET) and e2f-1 transcription factor in primary lesion of gastric adenocarcinoma (GC).MethodTissue samples from the primary lesion of GC in patients who accepted D2/D3 radical gastrectomy with R0/R1 resection were stained by immunohistochemistry of c-MET, p-MET, e2f-1 and Ki-67. The univariate and the multivariate analyses involving in clinicopathological parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
(27 reference statements)
5
22
1
Order By: Relevance
“…Moreover, p-MET staining is more convenient compared with MET FISH and may act as a substitute method for choosing patients for anti-MET treatment. To date, several studies have evaluated p-MET expression in gastric cancer (36)(37)(38)(39), and the results were inconsistent. The p-MET-positive rate of 6% (8/134) observed in our study is similar to the rate reported by Janjigian and colleagues, who also used the same antibody that recognizes p-MET at Y1234/1235 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, p-MET staining is more convenient compared with MET FISH and may act as a substitute method for choosing patients for anti-MET treatment. To date, several studies have evaluated p-MET expression in gastric cancer (36)(37)(38)(39), and the results were inconsistent. The p-MET-positive rate of 6% (8/134) observed in our study is similar to the rate reported by Janjigian and colleagues, who also used the same antibody that recognizes p-MET at Y1234/1235 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al analyzed 120 primary gastric cancer specimens and determined the presence of c-MET overexpression in approximately 66 % of them. Of particular significance, the authors identified a high rate of p-MET positivity (59 %) suggesting activation of MET tyrosine kinase activity [71]. In keeping with the results of previous studies, MET overexpression was found to represent an independent marker of poor prognosis [71].…”
Section: Metmentioning
confidence: 57%
“…MET protein expression on immunohistochemistry (IHC) is predominantly detected in cytoplasm of tumor cells, but is also found in the cell membrane [12,[18][19][20] . Lee et al [12] assessed membranous MET expression according to a standardized technique, similar to that used to evaluate HER2 expression.…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%
“…Retterspitz reported that MET was overexpressed in 51% (45 of 88) of diffuse type tumors [24] . MET overexpression has been significantly associated with tumor invasion depth [12,13,23] , lymph-node metastasis [12,13,19,20,25,26] , distant metastasis [12,13,25] , tumor stage [12,20,23,26] , and recurrence [14] , although several studies found no relation to any clinicopathological factors [24,27,28] . MET overexpression correlated with liver metastasis only in stage Ⅳ disease [29] .…”
Section: Protein Expression On Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation